X band electron paramagnetic resonance spectrometer based on field programmable gate array - Eow, Wei Siang (2022)
Electron Paramagnetic Resonance (EPR) is a phenomenon based on Zeeman interaction. To study this phenomenon, a spectrometer is needed. Conventional spectrometers are using benchtop Arbitrary Wave Generator (AWG) or microwave synthesizer as microwave source for continuous wave mode and pulsed mode. However, there are few disadvantages with these instruments. Field Programmable Gate Array (FPGA) is another alternative to AWG due to it advantages such as high flexibility, low profile size and low cost. In this work, a X band FPGA based EPR spectrometer and a loop gap resonator were designed, simulated and built to detect EPR signals. The resonator was measured and found to have an unloaded resonance frequency of 8.852 GHz and Q-factor of 646.0 whereas the loaded resonance frequency was 8.668 GHz with a Q-factor of 615.8. This spectrometer was successfully used to detect EPR signal in an external magnetic field from 311.2 to 311.8 mT with a signal-to-noise ratio (SNR) of 18 ± 8. Based on the experimental parameters, the 2,2-diphenyl-1- picrylhydrazyl (DPPH) g-factor from the developed spectrometer was measured to be 1.9945 ± 0.0012. This value is very close to the DPPH standard value 2.003. Using the designed resonator and DPPH sample, the spectrometer performance such as signal purity, SNR and sensitivity was determined. This spectrometer has the potential to be modified to pulsed mode by installing certain components such as pulse amplifier and power attenuator.